Susceptibility of Tribolium castaneum and Trogoderma variabile larvae and adults exposed to methoprene-treated woven packaging material. (September 2017) - Scheff, Deanna S.; Subramanyam, Bhadriraju; Arthur, Frank H.
Abstract: Methoprene is an insect growth regulator (IGR) registered in the United States for direct application to stored raw grains, as an aerosol or residual contact insecticide, and for use as a coating for protection of packaged products. A series of tests was conducted to determine the adverse effects of short term exposure, sub-lethal exposure, and continual exposure of the red flour beetle, Tribolium castaneum (Herbst) and warehouse beetle, Trogoderma variabile Ballion, on methoprene-treated woven packaging material at 27 and 32 °C and 60% r.h. In the first test, larvae of both species were added to individual arenas and exposed for different time intervals, removed and resulting adult emergence was assessed. In the second test, eggs of both species were exposed on the packaging surfaces to determine percent egg hatchability. In the third test, adults of T. castaneum and T. variabile were added to arenas and held for 7 and 3 d, respectively, to determine number of eggs laid per female and subsequent egg hatchability. The eggs were held in arenas to determine the effect of continual exposure on egg-to-adult emergence. Results showed normal adult emergence decreased with increasing exposure time and temperature. Exposure to methoprene-treated packaging did not adversely affect fecundity of T. variabile adults, but did affect fecundity of T. castaneum . Continual exposure gave 100% suppression of T. castaneum adult emergence and a reduction of T. variabile emergence. This study indicated that methoprene-treated packaging could be a valuable addition to an existing integrated pest management program to increase protection of packaged products. Highlights: Egg-to-adult emergence of two insect species was reduced on methoprene-treated packaging. Methoprene inhibited 100% of Tribolium castaneum adult emergence. Methoprene adversely affected only T. castaneum fecundity. T. castaneum and T. variabile egg hatchability decreased at 32 °C than at 27 °C. T. castaneum was more susceptible to methoprene packaging than T. variabile.